A detailed study on the effects of sunshape and incident angle on the optical performance of parabolic trough solar collectors. (5th November 2017) - Zou, Bin; Yang, Hongxing; Yao, Yang; Jiang, Yiqiang
Highlights: Effects of sunshape and incident angle on optical performance are studied. Both energy proportion in any angular span and end loss are theoretically derived. The acceptance-rejection sampling method is used to reduce computing time. Parameter study of the optical efficiency of the PTC is conducted. Effects of sunshape and incident angle on optical efficiency are remarkable. Abstract: The influences of sunshape and incident angle on the optical performance of the parabolic trough solar collector (PTC) are investigated comprehensively based on Monte Carlo Ray Tracing (MCRT) method and theoretical analysis. This study adopts the acceptance-rejection sampling method, instead of the direct sampling method, for random variable sampling to reduce computing complexity. Both the energy proportion bounded by any angle span in the optical cone and the end loss caused by any incident angle are derived theoretically. It is revealed that the sunshape has great effects on the optical performance of a PTC, which should be taken into consideration in practice. The geometrical configuration of the PTC, especially the absorber tube diameter, should be determined to meet the energy requirement based on local sunshape (circumsolar ratio) conditions. It is also found that the end loss, caused by the incident angle, weakens the optical efficiency. Larger aperture width and smaller absorber diameter will cause greater end loss for constant incident angle. When the absorber length is long enough, the effect of incident angle will be negligible. In a range of small focal lengths, the optical efficiency increases with the increase of focal length, and then decreases constantly with further increasing focal length. Findings in this paper can be used as reference or guidance for designing and optimizing PTC's structure in practice.